Effect of a Novel Handheld Photobiomodulation Therapy Device in the Management of Chemoradiation Therapy-Induced Oral Mucositis in Head and Neck Cancer Patients: A Case Series Study - In-Young Jo; Hyung-Kwon Byeon; Myung-Jin Ban; Jae-Hong Park; Sang-Cheol Lee; Yong Kyun Won; Yun-Su Eun; Jae-Yun Kim; Na-Gyeong Yang; Sul-Hee Lee; Pyeongan Lee; Nam-Hun Heo; et al. (Photonics, 2023)
Oral mucositis (OM) is a debilitating adverse event in patients undergoing treatment for cancer. This study aimed to evaluate the therapeutic effect of a novel handheld photobiomodulation therapy (PBMT) device on chemoradiation therapy (CRT)-induced OM in patients with head and neck cancer. Head and neck cancer patients undergoing CRT who developed moderate-to-severe OM during treatment were enrolled. After PBMT and at 2 and 4 weeks after PBMT, the mean value of OM grade decreased significantly from 2.63 to 2.13, 1.31, and 0.75, respectively (p < 0.05, p < 0.001, and p < 0.001). Moreover, we observed significant improvement in health-related quality of life (HRQoL) after PBMT compared to baseline through a validated questionnaire; EORTC QLQ-C30. In the present study, the use of this PBMT device in the management of CRT-induced OM in patients with head and neck cancer was generally well tolerated and resulted in the improvement of OM. However, evidence supporting its use remains lacking owing to limitations such as the small number of participants and lack of a control group. Therefore, further mechanistic studies and large-scale randomized controlled trials are needed to confirm the effectiveness of PBMT in the treatment of CRT-induced OM, as shown in our results.